Isolation, characterization and sequence determination of Noda virus from sea bass (Dicentrarchus labraxL.) reared in freshwater and marine facilities in Greece - XYLOURI (Ε. ΞΥΛΟΥΡΗ) E.; KOTZAMANIS (Ι. ΚΟΤΖΑΜΑΝΗΣ) J.; ATHANASSOPOULOU (ΑΘΑΝΑΣΟΠΟΥΛΟΥ Φ.) F.; DONG, L.; ARGYROKASTRITIS (ΑΛ. ΑΡΓΥΡΟΚΑΣΤΡΙΤΗΣ) A.; FRAGKIADAKI (ΕΙΡ. ΦΡΑΓΚΙΑΔΑΚΗ) E. (Journal of the Hellenic Veterinary Medical Society, 2017)
The present study aims το characterize Noda virus isolates from freshwater and marine fish, specifically from species Dicentrarchus labrax (sea bass). Previous works reported the detection of Noda virus only by using PCR, in cultured Dicentrarchus labrax showing clinical symptoms. Here we describe the isolation of Noda virus from symptomatic sea bass cultured in sea and freshwater facilities in Greece. The virus was isolated in the continuous cell line SSN -1, exhibiting characteristic cytopathic effect, vacuolation and degeneration of the monolayer. In parallel, in all cerebral tissue samples isolated from infected individuals, a 255 bp viral fragment has been detected, using Reverse Transcription - Polymerase Chain Reaction (RT-PCR) and nested PCR. Comparison of the amplified sequence was detected in diseased fish in European farms and in other piscine species revealed a high nucleotide homology.